A FATAL CASE OF 'PRIMARY' HEADACHE. Issue 11 (9th October 2013) - Dayanandan, Rejith; Bindman, Dorothea; Chhetri, Suresh Kumar; Jacob, Joseph; Mathur, Sachin; Mills, Roger John
Abstract : We describe a case of a 33 year old caucasian male with a subacute history of headaches presenting to the medical team with pyrexia, confusion and hallucinations. He subsequently became disorientated, agitated and initially needed sedation and ventilation after becoming acutely hypoxic with autonomic instability. He was subsequently found to have dense, pre–geniculate blindness and generalised arreflexia. Magnetic resonance imaging demonstrated normal brain parenchyma but diffuse nodular thickening and enhancement of the basal leptomeninges in the brain and throughout the entire spinal cord. Lumbar puncture revealed markedly xanthochromic CSF with opening pressures that were persistently raised above 40 cm CSF. CSF protein was elevated at 8–9 g/l; the CSF white cell count was never significantly elevated. Repeated cytological analysis of the spinal fluid failed to reveal any evidence of malignant cells. The patient was aggressively treated with anti–tuberculous chemotherapy and high dose dexamethasone as well as broad–spectrum antibiotics and a course of aciclovir. There was an encouraging, but transient, clinical improvement with a corresponding improvement in CSF protein, but thereafter the patient continued to deteriorate. A lumbar drain was inserted in order to control his elevated CSF pressure. Subsequent microbiological testing for HIV, syphilis, cryptococcal antigen, bacterial culture and viral PCR was negative; repeated TB cultures of CSF and sputum, CSF TB PCR and Quantiferon test were negative. An initial brain biopsy of non–dominant frontal lobe, which included the meninges, failed to identify any significant pathology. A second biopsy of the leptomeninges taken from the high cervical cord revealed the presence of a high grade astrocytoma and confirmed the final diagnosis of primary diffuse leptomeningeal gliomatosis (PDLG). The patient was not fit for any oncological intervention and died within 3 weeks of diagnosis. Leptomeningeal metastases from gliomatous brain tumours are seen occasionally and are well recognised but primary diffuse leptomeningeal gliomatosis is a very rare presentation of disseminated glial malignancy. Such cases are often treated initially as tuberculous meningitis. Our case highlights the difficulty in diagnosing this rare condition which should be remembered as an important differential in cases of basal leptomeningitis, particularly in those not responding to antimicrobial treatment.